THE ROLE OF THE KOPASSUS 81 UNIT IN DEALING WITH CYBER TERRORISM: A CONFLICT RESOLUTION EFFORT IN INDONESIA - Arifuddin Uksan; Pujo Widodo; Herlina Saragi (Bajang Institute, 2023)
Facing the current developments in the global environment, terrorist groups have been able to utilize cyberspace to carry out acts of terrorism against vital national installations and national information infrastructure. The rise of cyber crimes in the form of identity fraud, child pornography, fraud, and digital-based terrorism are threats that must be faced by all components of the nation. If this problem is not prevented from developing immediately, then a series of other problems will surface and more and more individuals will be affected by terrorism via cyberspace, so that cyberterrorist groups will be free to carry out their actions. In an effort to prevent the threat of cyber terrorism in Indonesia, the role of the 81 anti-terror Special Forces Unit is needed which specifically handles the threat of terrorism in an offensive and optimal manner. This study aims to analyze the role of the Kopassus Unit 81 in preventing the threat of terrorism, by choosing a qualitative research method. From the results of the research it was found that the development of cyber terrorism threats in Indonesia is very advanced and dangerous, for this reason an optimal role is needed from the Kopassus unit in dealing with cyber terrorism threats to support national defense. This study concludes that progress in the field of science, especially Information and Communication Technology can have a negative impact in creating contemporary crimes known as cybercrimes so that this condition has the potential to increase the spectrum of threats to National Defense.Keywords: optimizatioan; kopassus; cyber terrorism; national defense.